Synthesis, in vitro activity, and computational evaluation of novel Thiadiazole derivatives as potent urease inhibitors - Naseer Ahmed; Kamran Mehdi; Obaid-ur-Rehman Abid; Saqib Khan; Adi T. Zikri; Is Helianti (Results in Chemistry, 2025)
A novel series of thiadiazole derivatives (6a-d) was synthesized through the cyclization of thiosemicarbazides using concentrated sulfuric acid. Structural confirmation was done by spectroscopy and elemental analysis. The synthesized compounds were evaluated for their urease inhibitory potential. To further investigate the kinetics and binding modalities of the synthetic compounds within the active sites of urease enzymes, molecular docking and MD simulations were run. The NH proton of thiadiazoles was detected in the region of 10.10–10.28 ppm, confirming the synthesis by a distinctive 1H NMR signal. At m/z 353, the EIMS spectra showed a peak for molecular ions, with an intensity ranging from 12 to 44 %. Compound 6a and 6d emerged as the most potent urease inhibitors, exhibiting IC₅₀ values of 43.7 ± 5.8 μM and 89.4 ± 5.8 μM, respectively. Molecular docking studies revealed strong binding affinities for 6a that is −7.35 kcal/mol and for 6d −7.44 kcal/mol, with both forming two hydrogen bonds within the enzyme's active site. Molecular dynamics (MD) simulations further validated the stability of 6a and 6d in the binding pocket over the simulation period, supporting their inhibitory mechanisms. Both wet-lab experiments and in silico studies confirmed that compounds 6a and 6d were the most potent urease inhibitors among the series.